Effect of preexercise meals with different glycemic indices and loads on metabolic responses and endurance running - Chen, Y. J.; Wong, S. H.; Wong, C. K.; Lam, C. W.; Huang, Y. J.; Siu, P. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
This study examined the effect of ingesting 3 isocaloric meals with different glycemic indices (GI) and glycemic loads (GL) 2 hr before exercise on metabolic responses and endurance running performance. Eight male runners completed 3 trials in a randomized order, separated by at least 7 days. Carbohydrate (CHO) content (%), GI, and GL were, respectively, 65%, 79, and 82 for the high-GI/high-GL meal (H-H); 65%, 40, and 42 for the low-GI/low-GL meal (L-L); and 36%, 78, and 44 for the high-GI/low-GL meal (H-L). Each trial consisted of a 1-hr run at 70% VO2max, followed by a 10-km performance run. Low-GL diets (H-L and L-L) were found to induce smaller metabolic changes during the postprandial period and during exercise, which were characterized by a lower CHO oxidation in the 2 trials (p < .05) and a concomitant, higher glycerol and free-fatty-acid concentration in the H-L trial (p < .05). There was no difference, however, in time to complete the preloaded 10-km performance run between trials. This suggests that the GL of the preexercise meal has an important role in determining subsequent metabolic responses.